Mechanical properties of particleboard using acacia mangium wood particles binded with seaweed-based adhesives - Liew, Kang Chiang; A R Samin (Institute of Physics Publishing, 2021)
The purpose of this study was to evaluate the mechanical properties of particleboards made from Acacia mangium wood particles binded with three different types of seaweed-based adhesive. Red seaweed (RS), brown seaweed (BS) and green seaweed (GS) were used as the seaweed-based adhesives., while particleboard using urea formaldehyde (UF) adhesive was produced as control. Adhesives and wood particles were mixed and then undergone mat-forming, pre-pressing, hot-pressing and conditioning process. The test pieces for bending test (Modulus of Elasticity, MOE; Modulus of Rupture, MOR), and internal bonding strength (IB) were cut into size according to JIS A 5908: 2003. From mechanical properties results attained, for internal bonding strength test, all boards using RS, BS and GS adhesives were found to be significantly different at p≤0.05. Apart from that, RS adhesive showed highest MOE and MOR at 529.4259 N/mm2 and 1.7900 N/mm2, respectively. As a conclusion, the mechanical properties of particleboard using RS, BS, and GS adhesives showed RS stands out as the better adhesive among them which have significant effects on its strength.